Longitudinal changes of fractional anisotropy in Alzheimer’s disease patients treated with galantamine: a 12-month randomized, placebo-controlled, double-blinded study - Likitjaroen, Y.; Meindl, T.; Friese, U.; Wagner, M.; Buerger, K.; Hampel, H.; Teipel, S. J. (European archives of psychiatry and clinical neuroscience, 2012)
Diffusion tensor imaging (DTI) demonstrates decline of fractional anisotropy (FA) as a marker of fiber tract integrity in Alzheimer’s disease (AD). We aimed to assess the longitudinal course of white matter microstructural changes in AD and healthy elderly control (HC) subjects and to evaluate the effects of treatment with the cholinesterase inhibitor galantamine on white matter microstructure in AD patients. We enrolled 28 AD patients and 11 healthy elderly control subjects (HC). AD patients were randomly assigned to 6-month double-blind galantamine treatment or placebo, with a 6-month open-label extension phase. DTI was performed at baseline, as well as at 6 and 12-month follow-up in AD patients. The HC subjects underwent DTI at baseline and 12-month follow-up without treatment. We measured FA in regions of interest covering the posterior cingulate and corpus callosum. At 6-month follow-up, the AD group showed significant FA decline in the left posterior cingulate. FA decline was significantly preserved in the posterior body of the corpus callosum in AD group with treatment compared to placebo. At 12-month follow-up, the AD patients showed no differences in FA decline between initial treatment and placebo groups after the 6-month open-label extension phase. A significant FA decline occurred in the left posterior cingulate across the AD and HC groups without between-group differences. DTI demonstrated FA decline in intracortically projecting fiber tracts in aging and AD over 1 year. Galantamine had limited impact on regional FA decline, which was not preserved after additional 6-month open-label treatment.